An approach to functional description of mass-operational characteristics in the tasks of quality control of raw materials - Sandulyak, Darya; Sandulyak, Anna; Polysmakova, Maria; Sandulyak, Alexander; Solovev, Nikita (Journal of Innovative Applied Mathematics and Computational Sciences, 2025)
The paper presents a mathematical approach to solving an applied problem, namely determining the content of metal-containing impurities in the building industry. An example involving the magnetic control of a quartz sand sample is considered. The results are presented graphically and additionally processed in semi-logarithmic coordinates. Using the proposed method, the total mass of impurities in the sample was calculated, as well as the mass removed during a limited number of operations for extracting metal impurities, and the consistency of the control was assessed.